Human trafficking and the mental health burden of refugees in Germany [data] - Dönnhoff, Ivo; Tambini Stollwerck, Estella; Rzepka-Marot, Irja; Friederich, Hans-Christoph; Nikendei, Christoph (Universität, 2025)
In this study we researched the association between human trafficking and mental disorders. In a large observational study with 1108 asylum seekers in a german refugee reception center we found human trafficking to be strongly associated with several mental disorders: depression, anxiety disorders and PTSD. This dataverse contains our collected data as well as the R code used for analysis. We also provide the RMarkdown files with our results. To prevent any kind of tracing, we had to omit country of origin, language and religion in the raw data set. This was done to ensure the safety of this vulnerable group of participants.
Gefördert durch: Ministry of Justice and Migration Baden-Württemb: DMA-ID 11537
Gesehen am 17.04.2025
Keywords: Forschungsdaten; Datenbank